Gross anatomy - Halliday, Nancy L.; Chung, Harold M.; Chung, Kyung Won. (Philadelphia : Wolters Kluwer Health, 2024)
The Board Review Series (BRS) is aimed at providing basic knowledge as it relates to clinical situations and is used by students studying for board and course exams. BRS Gross Anatomy prepares students for first-year anatomy course exams and the USMLE Step 1 board exam. This easy-to-use resource presents the essentials of human anatomy through concise descriptions, clinical correlations, radiographs, full-color illustrations, and tables--Provided by publisher.
Preceded by Gross anatomy / Kyung Won Chung, Harold M. Chung, Nancy L. Halliday.
Includes index.
Keywords: Anatomy